Modelo matemático de evolução microestrutural de fio-máquina microligado ao nióbio laminado a quente - Felipe Gabriel de Oliveira (2016)
Niobium microalloyed steels are very important for applications requiring high strength and toughness, as in the case of oil platforms, ships, pipelines, transmission towers, bridges and buildings. The presence of niobium in the steel promotes grain refinement of austenite during hot rolling, and leads to hardening due to formation of fineprecipitates dispersed in the material. Knowing how process variables affect the development of the grain size during hot rolling is very important. This paper presents a study of the equations that describe properly the growth kinetics of austenite grain in the rolling wire rod. Thus, these equations are used to develop a mathematical model for predicting mechanical properties. A new form of equivalent deformation calculationfor non-planar sections was used successfully. The results of the modeling were compared to results obtained from test samples collected from industrial experiments and compared the results already published in the literature. For both cases the model proved to be an important tool for compute the final mechanical properties of niobi microalloyed steels.